Perceptual Aspects of Tuning in a Balinese Gamelan Angklung for North American Students - Rahn, Jay (Canadian University Music Review / Revue de musique des universités canadiennes, 1996)
A detailed analysis of the spectra and frequencies of tones produced on metallophones in a Balinese orchestra clarifies a number of issues that arise in studying timbre and tuning. Among these are the relative importance of accuracy and completeness of measurements, the relevance of acoustical description to musical perception and style, the appropriateness of statistical generalizations and numerical formulations to musical practice and theory, and the possibility of bi-musical responses to divergent tuning systems. Byproducts of the investigation include a proposed basis for inter-cultural ear training and a novel formulation of the unison, octave, and other intervals (including wide and narrow variants), as well as traditional scales and interval collections that have existed side-by-side in widely varying forms within individual cultures.